Politik Kepentingan : (Analisis Historis Kasus Ab? Muslim al-Khurasan? di Masa Daulah Umaiyah dan Abbasiyah) - Nasution, Syamruddin (Faculty of Sharia and Law - Sunan Kalijaga State Islamic University, 2013)
At the end of 2013 and beginning of 2014 we were presented thespectacle of government for maintaining political interests, that was the arrestof a number of politicians, and among them is the suspects in the Hambalang,Anas Urbaningrum, and Antasari Azhari before, chairman of the CorruptionEradication Commission (KPK). Two of these cases may be as a representativeexample of the case that the same modus, are killing characters of politicionfor political interests. It turns out that these cases also occurred in early Muslimhistory, even kill each other. One example was the case of Ab? Muslim alKhurasan?, one of the major meritorious and has a big hand in toppling UmaiyahDaulah and established the Abbasid Daula. Initially Abu Muslim was appointedby Ab? Abb?s a?-?affah, the first Caliph of the Daulah Abbasid, to becomegovernor of Khurasan, but was then killed by Abu Jafar al-Mansur, 2nd Caliphof Abbasids. This paper attempts to describe the case of Ab? Muslim alKhurasan?, a politician who was killed by his own at the beginning of the DaulahAbbasid. This study addresses three problems. First, how the events that befallAb? Muslim al-Khurasan?. Secondly, why Ab? Muslim al-Khurasan? was killed.Third, what is the relevance of studying and knowing murder of Ab? Muslimal-Khurasan? to political life in Indonesia by contextualization.